Fitting the best-fit distribution for the hourly rainfall amount in the Wilayah Persekutuan - Y., Fadhilah; M. D., Zalina; V. T. V., Nguyen; S., Suhaila; Y., Zulkifli (Penerbit UTM Press, 2007)
In determining the best-fit model for the hourly rainfall amounts for the twelve stations in the Wilayah Persekutuan, four distributions namely, the Exponential, Gamma, Weibull and Mixed-Exponential were used. Parameters for each distribution were estimated using the maximum likelihood method. The best-fit model was chosen based upon the minimum error produced by the goodness-of-fit tests used in this study. The tests were justified further by the exceedance probability plot. The Mixed-Exponential was found to be the most appropriate distribution in describing the hourly rainfall amounts. From the parameter estimates for the Mixed-Exponential distribution, it could be implied that most of the hourly rainfall amount recorded were received from the heavy rainfall even though there was a high occurrences of light rainfall.